2021
DOI: 10.3390/cryst11020115
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calcination Temperature on Crystal Growth and Optical Characteristics of Eu3+ Doped ZnO/Zn2SiO4 Composites Fabricated via Simple Thermal Treatment Method

Abstract: This research paper proposes the usage of a simple thermal treatment method to synthesis the pure and Eu3+ doped ZnO/Zn2SiO4 based composites which undergo calcination process at different temperatures. The effect of calcination temperatures on the structural, morphological, and optical properties of ZnO/Zn2SiO4 based composites have been studied. The XRD analysis shows the existence of two major phases which are ZnO and Zn2SiO4 crystals and supported by the finding in the FT-IR. The FESEM micrograph further c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
(90 reference statements)
2
10
0
Order By: Relevance
“…The particle size grew rapidly as the temperature rose from 600 to 800 °C. These findings could imply that the increase in size was mainly due to crystal development, as evidenced by multiple previous investigations [ 59 , 60 ]. When these two parameters (voltage and calcination temperatures) are combined, they have a more significant impact on particle size, comparable to the effects seen in Figure 3 a,b.…”
Section: Resultssupporting
confidence: 65%
“…The particle size grew rapidly as the temperature rose from 600 to 800 °C. These findings could imply that the increase in size was mainly due to crystal development, as evidenced by multiple previous investigations [ 59 , 60 ]. When these two parameters (voltage and calcination temperatures) are combined, they have a more significant impact on particle size, comparable to the effects seen in Figure 3 a,b.…”
Section: Resultssupporting
confidence: 65%
“…The XRD analysis showed that the intensity of the XRD peaks indicated the distinctive patterns and suggested the formation of crystalline MgO NPs samples at 400, 500, and 600 °C for 3 hours. As the calcination temperature increased, it was observed that the peaks became higher and sharper due to agglomeration, and crystallite size increased [28].The FE-SEM image showed that the diameter of MgO nanoparticles is significantly larger than the size of crystallites as revealed by XRD.…”
Section: Discussionmentioning
confidence: 95%
“…The band gap value decreases as the calcination temperature increases because the material was tending towards the more ordered structure and fewer imperfection, which directly influenced the intermediate energy level distribution within the valence and conduction bands. 48,49…”
Section: Resultsmentioning
confidence: 99%